The Prospects of Using Chilled Semen to Increase the Production of Dairy Cattle - Situmorang, Polmer (Indonesian Animal Sciences Society, 2003)
Dairy cattle production in Indonesia has been rapidly developed since the importation of live cattle from Australia and New Zealand in 1970. Technology of artificial insemination (AI) play an important role to increase the production of dairy cattle by using frozen semen from both importation or produced in Centre for Artificial Incemination Lembang and Singosari. Nevertheless, frozen semen is not without problems because a more than less 30% of sperm are killed during the freezing procedure and those who survive are sensitive to enviroment and has a low fertility. Therefor the using of chilled semen will be an alternative to be considered to replace frozen semen. Chilled semen can be simply produced and not required a complex laboratory and an expensive equipment. Other advantages is the production of straw per bull and fertility was higher than those frozen semen and resulting an increased of farmer income. Case study in Pangalengan West-Java showed a lower production cost of chilled semen than those cost for purchasing frozen semen. Widely aplication of the using of chilled semen will reduce a dependency on frozen semen and importation of bull, and at the end will increase the national income. Â Keywords: Dairy cattle, frozen semen, chilled semen